(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Analysis of physicochemical characteristics of samples of rain water collected from rain gauges at two sampling stations at Orji and Umuchima-Ihiagwa in Owerri, Nigeria revealed that rain water from sampling station, Orji (RWSO) had the highest pH value (6.24), while values obtained for total suspended solids (14.23 mg/l-1), total dissolved solids (15.10 mg/l-1), calcium hardness (3.91 mg/l-1), and sulphate (11.23 mg/l-1) were highest for RWSO compared to values obtained from analysis of rain water sampling station, Umuchima (RWSU). However, it was observed that values obtained from nitrate analysis were almost equal (0.62, 0.60 mg/l-1 for RWSO and RWSU) for both sampling stations. Values obtained for the physicochemical parameters from both sampling stations were within World Health Organization (WHO) permissible standards for quality drinking-water.